Поезія Тараса Шевченка в польських перекладах ХХ століття - Астаф’єв, О. (Слово і Час, 2013)
У статті розкрито специфіку польських перекладів творів Т. Шевченка у ХХ ст., подано типологію
перекладацьких моделей, проаналізовано засоби відтворення символіки, ритміки, лексики,
тропіки, фразеології, строфічних форм. The article explores the specifics of Polish translations of Taras Shevchenko’s texts made during the
20th century. It also provides the typology of translation models and analyzes the ways to reproduce
the symbols, rhythm, vocabulary, tropics, phraseology and strophic form of the original used by Polish
translators. В статье раскрыта специфика польских переводов
Т. Шевченко в ХХ в., представлена типология
переводческих моделей, проанализированы средства
воссоздания символики, ритмики, лексики, тропики,
фразеологии, строфических форм.